2008
DOI: 10.1111/j.1745-7254.2008.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal ribosome entry site ofRhopalosiphum padivirus is functional in mammalian cells and has cryptic promoter activity in baculovirus-infected Sf21 cells1

Abstract: Aim: To substantiate the in vitro translational studies of a cross-kingdom, internal ribosome entry site (IRES), the 5´untranslated region of the Rhopalosiphum padi virus (RhPV), can function in mammalian cells and act as a shuttle IRES between insect cells and mammalian cells. Methods: Cytomegalovirus (CMV) promoter-based bicistronic mammalian cell expression vectors, either in plasmids or baculovirus vectors, were generated. Plasmid transient transfection and baculovirus transduction assays were performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…
Figure 4Efficiency of baculovirus-incorporated promoters in C6/36 cells. ( a ) Schematic representation of transfer vectors used to generate the recombinant baculoviruses expressing EGFP driven by several baculovirus, mammalian viral, and mosquito host promoters from the following genes: pag1 , a HzNV-1 viral early expressing gene 23 ; p10 , baculovirus late gene 46 ; cmv , cytomegalovirus 47 ; sv40 , simian virus 40 24 ; cir , chimeric internal ribosome entry site (IRES) of RhPV virus and EV71 virus 48,49 ; b1 , cecropin b1 gene 50 ; pub , polyubiquitin gene 42 and a4 , defensin a4 gene 51 . ( b ) Fluorescence images.
…”
Section: Resultsmentioning
confidence: 99%
“…
Figure 4Efficiency of baculovirus-incorporated promoters in C6/36 cells. ( a ) Schematic representation of transfer vectors used to generate the recombinant baculoviruses expressing EGFP driven by several baculovirus, mammalian viral, and mosquito host promoters from the following genes: pag1 , a HzNV-1 viral early expressing gene 23 ; p10 , baculovirus late gene 46 ; cmv , cytomegalovirus 47 ; sv40 , simian virus 40 24 ; cir , chimeric internal ribosome entry site (IRES) of RhPV virus and EV71 virus 48,49 ; b1 , cecropin b1 gene 50 ; pub , polyubiquitin gene 42 and a4 , defensin a4 gene 51 . ( b ) Fluorescence images.
…”
Section: Resultsmentioning
confidence: 99%
“…TAAG sequences are relatively rare in the AcMNPV genome and are found primarily in late or very late promoter regions [ 20 ]. However, the cDNA of the RhPV 5′UTR IRES possesses six TAAG motifs and can act as a cryptic promoter in baculovirus-infected Sf21 cells [ 19 ]. In order to characterize which of the six TAAG motifs mediated the promoter activity, truncated RhPV 5′UTR sequences were produced by making stepwise deletions from either ends; then, these truncated sequences were subject to functional promoter assays.…”
Section: Resultsmentioning
confidence: 99%
“…The M300/429 fragment that spans the RP110 promoter region also exhibited IRES activity in all of the tested translation systems [ 24 ]. Our previous studies also demonstrated that the 579 nts RhPV 5′UTR function as an IRES, but not as a promoter, in mammalian cells [ 19 ]. Thus, it would be interesting to explore whether the 110 nt RP110 promoter or any other constructs listed in Figure 1 A can function as an IRES element in mammalian cells, given that no promoter activity was found in vCMV-DRhir(L1-2)E, vCMV-DRhir(L5-6)E or vCMV-DRhir(L6)E infected Sf21 cells ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Spodoptera frugiperda IPBL-Sf21 (Sf21) cell line was cultured in TNM-FH insect medium containing 8% heat-inactivated fetal bovine serum (FBS) at 27 °C [ 68 ]. The U-2OS (human osteogenic sarcoma cell line, purchased from Bioresource Collection and Research Center 331, Shih-Pin Rd., Hsinchu 300193, Taiwan) cells were grown in McCoy’s medium supplemented with 10% fetal bovine serum [ 69 ]. Cellfectin (Invitrogen, Carlsbad, CA, USA) was used for transfection in Sf21 cells according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%